Analisis Pengangguran Terbuka Di Provinsi Jawa Tengah Tahun 2015-2019 - Zila Anggraini Anggraini (Program Studi Ekonomi Pembangunan Universitas Muhammadiyah Malang, 2021)
Unemployment is one of the problems in economic development in every country. If the amount of eviction is high, it can cause social insecurity and worsen existing poverty. This study aims to determine the effect of Education Level and PMDN on Open Unemployment in Districts and Cities of Central Java Province in the period 2015-2019. Analysis techniques using the data panel regression analysis method and traditional assumptions using the Eviews 9 tool. This study showed that simultaneously the variable Level of Education and PMDN had a significant effect on Open Unemployment in Districts and Cities of Central Java Province in 2015-2019. At the same time, partially variable Education Level has a significant negative effect on Open Unemployment in districts and cities of Central Java Province. The variable Domestic Investment (PMDN) has an insignificant positive impact on Open Unemployment in Districts and Cities of Central Java Province in 2015-2019.